Acute pancreatitis after pancreatoduodenectomy: clinical outcomes and predictive factors analysis according to the International Study Group of Pancreatic Surgery definition. Issue 3 (March 2023) - Quero, Giuseppe; Massimiani, Giuseppe; Lucinato, Chiara; Fiorillo, Claudio; Menghi, Roberta; Laterza, Vito; Schena, Carlo A.; De Sio, Davide; Rosa, Fausto; Papa, Valerio; Tortorelli, Antonio P.; Tondolo, Vincenzo; et al.
Abstract: Background: Post-pancreatectomy acute pancreatitis (PPAP) is an increasingly described complication after pancreatic resection. No uniform definition criteria were present in the literature until the recent proposal of the International Study Group of Pancreatic Surgery (ISGPS). Aim of this study is to evaluate the clinical significance of the novel ISGPS definition of PPAP. Methods: Patients who underwent pancreatoduodenectomy (PD) between 2006 and 2022 were enrolled. PPAP was defined and graded according to the ISGPS criteria. Results: Among 520 PDs, 120 (23%)patients developed post-operative hyperamylasemia (POH), while PPAP occurred in 63(12.1%) cases. PPAP occurrence related to a higher rate of more severe complications (48–76.1%vs118–25.8%; p < 0.0001), delayed gastric emptying (DGE) (27–42.9%vd114–24.9%; p = 0.003) and post-operative pancreatic fistula (POPF) (57–90.5%vs186–40.8%; p < 0.0001). When stratified for PPAP severity, grade B and C patients more frequently developed major complications (p < 0.0001), POPF (p < 0.0001), DGE (p = 0.02) and post-operative hemorrhage (p < 0.0001) as compared to POH. At the multivariable analysis, soft pancreatic texture (p = 0.01)and a Wirsung diameter ≤3 mm (p = 0.01) were recognized as prognostic factors for PPAP onset, while a pancreatic duct ≤3 mm was the only feature significantly influencing a more severe course of PPAP (p = 0.01). Conclusion: The ISGPS classification is confirmed as a valuable method for a uniform definition and clinical course evaluation. Further studies in a prospective manner are still needed for a further confirmation.